A look back: Who should teach? Kappan authors weigh in. (November 2021) - Preston, Teresa
Kappan authors have expressed concern about the number and quality of teachers entering the workforce for at least 100 years. In this monthly column, Teresa Preston explores what authors have said about the personal qualities and training that teachers need. Common threads include a recognition that intelligence does not necessarily equate to teaching success and concern that alternate pathways were bringing unqualified teachers into classrooms .